Shelf life extension of virgin coconut oil through the addition of food grade desiccant - Cabisidan, Erliza Karen C. (2006)
ABSTRACT The efficacy of desiccants in inhibiting the development of hydrolytic rancidity in virgin coconut oil was studied. Silica gel and sodium chloride were added at 0.7% and 2.0% (w/w). The untreated virgin coconut oil had the highest free fatty acid Reichert-Meissl value, developed rancidity the fastest, and had the lowest viscosity among all the samples. Samples treated with silica gel generally had the lowest free fatty acid value. These samples also had the lowest Reichert-Meissl number but values generated from the analysis were below the 6-8 standard RM number. The viscosity of these oil samples generally decreased over time. Samples treated with sodium chloride had higher free fatty acid and Reichert-Meissl values than the samples treated with silica gel. These samples also became less viscous than the silica-treated virgin coconut oil samples. The untreated and NaCl-treated samples developed both rancid odor and taste, but remained colorless. No rancidity was observed in the silica-treated samples but the silica gel changed color from colorless to brown. Based on the above observations, silica gel appeared to be the best desiccant in virgin coconut oil.